Corpos Enlutados: Por um cuidado espiritual terapêutico em situações de luto - Paula, Blanches de (2009)
This thesis has as its objective to understand the phenomenon of grief by death based on phenomenology, and the experiences of members of the Methodist Church in Greater ABC. In order to reach this general objective, the specific objectives chosen were: dialogue with theoreticians in the areas of theology and psychology; understand the phenomenology of the existential body of Maurice Merleau-Ponty as the parameter for understanding the study of grief by death; contribute to research in the area of Spiritual Care in situations of grief by death. The theoretical-methodological approach has as its base the oral reports of ten persons that bring their present of grief via the guiding question: how did you experience your grief? After the literal transcriptions, these oral reports permitted the presentation of units of meaning and the establishment of analytical categories: pain, grief because of death, type of loss, disorganization of being, existential body, rationalization, health, anticipatory grief, the material dimension of living, guilt, memory, and serenity. Based on the categories, interpreted phenomenologicaly, via the construction of a nomoetic table it was possible to identify points of convergence and differences between the oral reports. In search for an understanding of the experience of grief, the reports were submitted to an ideographic analysis that is the attempt to recognize the individual psychology of the subjects of the research. The synthesis of thinking, as the expression of the phenomenology of grief, revealed nuances for pastoral praxis. The result of the construction of this new knowledge in terms of the experience of grief by death were significant in terms of certain perceptions: the process of grief in the context of institutional religion is similar to that of non-religious contexts; Christian theology has space for the resignification of death, by means of the creation of a spirituality for the process of dying and, for this to be possible, it is necessary, within religious communities, to develop a theology of loss that makes possible Christian Education directed to confronting grief, or, in other words, a theology the values life in the midst of loss; the body was the language most present in the experience of grief and, still, the grieving body is a paradox in the Christian Church, because of the tendency to not address the theme of body, in terms of faith education. The perception of the necessity of developing spiritual therapeutic care in the face of grief was clear in order to reach not only the individual in situations of loss, but also the community, as an integral part of public actions that address this question.(AU)